Ac Conductivity And Raman Spectroscopic Studies Of PrMnO3 Nanostructure. (2018) - Saha, Sujoy; Maity, Ritwik; Sakhya, Anup Pradhan; Chanda, Sadhan; Dutta, Alo; Sinha, T.P.
Abstract: In the present work the orthomanganite perovskite oxide PrMnO3 (PMO) is synthesized in the nano phase by using the sol-gel technique. The phase formation with Pnma symmetry of the sample is confirmed by the Rietveld refinement of X-ray diffraction data.The particle size of the sample is determined by Scanning electron microscopy. The Ac conductivity of PMO is studied in the frequency range from 42 Hz to 1.1 MHz and in the temperature range from 303 K to 573K which shows insulator to metal transition at 423 K. The band gap of the material is found to be 0.66 eV. The room temperature Raman spectrum is fitted with the sum of 24 Lorentzian peaks.